Cellular Automaton Models of Highway Traffic Flow Considering Lane-Control and Speed-Control - 钱勇生 李文俊 曾俊伟 王敏 杜加伟 广晓平 (Communications in theoretical physics, 2011)
As two kinds of management modes of highway tramc control, lane-control, and speed-control produce different effect under different conditions. In this paper, traffic flow cellular automaton models for four-lane highway system with two opposing directions under the above two modes are established considering car and truck mixed running. Through computer numerical simulating, the fundamental diagrams with different parameters are obtained, and after the analysis of density-flux diagrams, the variation discipline of flux with traffic density under different control models is gained. The results indicate that, compared with lane-control, utilization ratio of road can be further improved with speed-control when the truck number increases. The research result is of great significance for reasonable providing theoretical guidance for highway traffic control.